Molecular and in vitro biochemical assessment of chemosensory protein 10 from brown planthopper Nilaparvata lugens at acidic pH - Muhammad Irfan WARIS; Aneela YOUNAS; Rana Muhammad Kaleem ULLAH; Fatima RASOOL; Muhammad Muzammal ADEEL; Man-qun WANG (Journal of Integrative Agriculture, 2022)
Chemosensory proteins (CSPs) are important molecular components of the insect olfactory system, which are involved in capturing, binding, and transporting hydrophobic odour molecules across the sensillum in sensillar lymph in regulating insect behavior. This protein family (CSPs) is also involved in many other systems that are not linked to olfactory receptors in olfactory sensilla. The brown planthopper (BPH) is a monophagous pest of rice that causes damage by sucking phloem sap and transmitting a number of diseases caused by viruses. In this study, fluorescence competitive binding assay and fluorescence quenching assay at acidic pH were performed as well as homology modelling to describe the binding affinity of NlugCSP10. Fluorescence competitive binding assay (FCBA) demonstrated that NlugCSP10 bound strongly to nonadecane, farnesene, and 2-tridecanone at acidic pH. The results of FCBA indicated that NlugCSP10 bound different ligands at the physiological pH (5.0) of the bulk sensillum lymph. Fluorescence quenching assay demonstrated that NlugCSP10 generated a stable complex with 2-tridecanone, while two ligands nonadecane and farnesene collided due to molecular collisions. The interaction of selected ligands with the modelled structure of NlugCSP10 was also analyzed, which found the key amino acids (Gln23, Gln24, Gln25, Asn27, Met33, Ser34, Ile35, Tyr36, Asn42, Met43, Val45, Asn46, Asn93, Arg96, Ala97, Lys99, and Ala100) in NlugCSP10 that were involved in binding of volatile compounds. The present study contributes to the binding profile of NlugCSP10 that promotes the development of behaviorally active ligands based on BPH olfactory system.